Hardware Digital Banking Syariah: Tantangan dan Solusi - Rangkuti, Laila Rahmayuni; Anggreini, Maycika; Pratika, Ocha; Andrerico, Vicky Febima; N, Nurbaiti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The development of digital technology has brought major changes in the banking industry, including Islamic banking which is now increasingly focusing on digital banking services. This research aims to identify the challenges faced and solutions applied in the use of hardware, such as ATMs, in supporting Islamic digital banking services. By using a qualitative descriptive method through case studies, this study highlights the aspects of security, network stability, and hardware operational costs which are often the main obstacles. The findings suggest that some common issues, such as transaction failures due to unstable networks and high maintenance costs, affect service efficiency. To overcome these obstacles, Islamic banks are expected to improve control management over hardware and implement damage prevention measures. This research provides practical insights for Islamic banks in maximizing digital services and increasing customer satisfaction, as well as offering a theoretical foundation for the development of sharia-based digital banking systems in the future.